2003
DOI: 10.1029/2002gl016473
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the barotropic response of the global ocean to atmospheric wind and pressure forcing ‐ comparisons with observations

Abstract: [1] A global simulation of the ocean response to atmospheric wind and pressure forcing has been run during the Topex/Poseidon (T/P) period (1992 -2002), using a new hydrodynamic finite element (FE) model, MOG2D-G. Model outputs are compared to in situ observations with tide gauge data (TG) and bottom pressure gauge data (BPR), and also with T/P altimetric cross over points (noted CO). Intercomparisons were performed over the 1993 -1999 period. The model correction reduces the sea level variance by more than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
457
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(463 citation statements)
references
References 15 publications
6
457
0
Order By: Relevance
“…Bindoff et al, 2007). This was evidenced by the comparison between altimetrybased and steric trend patterns deduced from in-situ hydrographic measurements (Ishii and Kimoto, 2009;Levitus, 2005;Levitus et al, 2009;Lombard et al, 2005a, b) and ocean general circulation models (OGCMs) outputs (Wunsch et al, 2007;Kohl and Stammer, 2008;Carton and Giese, 2008;Lombard et al, 2009). Analyses of in situ ocean temperature measurements showed that the thermosteric component is the most important contribution to the observed sea level regional variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bindoff et al, 2007). This was evidenced by the comparison between altimetrybased and steric trend patterns deduced from in-situ hydrographic measurements (Ishii and Kimoto, 2009;Levitus, 2005;Levitus et al, 2009;Lombard et al, 2005a, b) and ocean general circulation models (OGCMs) outputs (Wunsch et al, 2007;Kohl and Stammer, 2008;Carton and Giese, 2008;Lombard et al, 2009). Analyses of in situ ocean temperature measurements showed that the thermosteric component is the most important contribution to the observed sea level regional variability.…”
Section: Introductionmentioning
confidence: 99%
“…It is corrected for the long wavelength orbit errors , ocean tides, and wet/dry troposphere and ionosphere (see Ablain et al, 2009 for more details). The inverted barometer (IB) correction has also been applied in order to minimize aliasing effects (Volkov et al, 2007) through the MOG2D barotropic model correction that includes the dynamic ocean response to short period (<20 day) atmospheric wind and pressure forcing and the static IB correction at periods above 20 day (see Carrere and Lyard, 2003 for details).…”
Section: Satellite Altimetry Sea Level Data (1993-2009)mentioning
confidence: 99%
“…A numerical model that accurately represents high-frequency sea level variability, such as the model of Carrère and Lyard (2003), would be very useful for removing high-frequency signals and thus leaving behind the lower-frequency sea level variability.…”
Section: November 2014 K U S a H A R A A N D O H S H I M Amentioning
confidence: 99%
“…Along track sea-level data are corrected for long wavelength errors (Traon et al 1998;Le Traon et al 2003) and an estimate of the inverse barometer (IB) effect is subtracted as well as wind and tidal effects in addition to other atmospheric corrections (taken together these are called dynamic atmospheric corrections; Carrère and Lyard 2003). The dynamic atmospheric Starting with different satellite along-track data, the different SLA signals are interpolated with objective analyses (Ducet et al 2000), thereby producing a field on a regular grid with a horizontal resolution of 1/8 • (∼ 13 km), every seven days.…”
Section: Satellite Datamentioning
confidence: 99%